The use of the Internet by people who die by suicide in England: A cross sectional study - Gunnell, D; Bennewith, O; Kapur, N; Simkin, S; Cooper, J; Hawton, K (2012)
Background: There is widespread concern regarding the possible influence of the Internet on suicidal behaviour. The aim of this study was to estimate the prevalence and characteristics of Internet-related suicide in England. Methods: Cross sectional study based on detailed review of the inquest reports of suicides occurring in the areas served by 12 Coroners in England. Evidence of Internet use in relation to the suicide was sought for each death. Results: Altogether inquest reports for 593 suicides (all methods) in 2005 and 166 suicides using specific methods in 2006-7 were assessed. There was evidence of a direct Internet contribution in nine (1.5% 95%CI 0.7 to 2.9%) of the 593 suicides in 2005. In seven (77.8%) of the cases the individuals had used the Internet to research the methods of suicide they used. Five (55.6%) individuals had used 'unusual' high-lethality methods, whereas such methods were only used in 1.7% of all suicides (p < 0.001). There was evidence of Internet involvement in 2.4% (0.7% to 6.1%) of the suicides in 2006-2007. None of the Internet-related suicides appeared to occur as part of a suicide pact. Limitations: The contribution of the Internet to suicide rates may be under-estimated in this analysis as Coroners are unlikely to comprehensively pursue the possibility of Internet involvement in all the deaths they investigate. Conclusions: Easy access to information about suicide methods and pro-suicide web sites on the Internet appears to contribute to a small but significant proportion of suicides. A key impact of the Internet appears to be in relation to information concerning suicide methods. © 2012 Elsevier B.V.